Electron contributions to the heat conduction across Au/graphene/Au interfaces. (May 2017) - Zhang, Chunwei; Chen, Weiyu; Tao, Yi; Zhao, Weiwei; Cai, Shuang; Liu, Chenhan; Ni, Zhenhua; Xu, Dongyan; Wei, Zhiyong; Yang, Juekuan; Bi, Kedong; Chen, Yunfei
Abstract: The thermal conductance across Au/graphene/Au and Au/hydrogenated graphene(H-graphene)/Au interfaces are measured using the time domain thermoreflectance (TDTR) technique. It is found that the thermal conductance decreases from 30 ± 5 MWm −2 K −1 to 14 ± 3 MWm −2 K −1 when the graphene is hydrogenated. However, nonequilibrium molecular dynamics (NEMD) simulation results show that the thermal conductance can be decreased by no more than 30% as the graphene is hydrogenated if only phonons are considered as the heat energy carriers. Considering the difference between the experimental and simulated results, we infer that electrons are involved in heat conduction across the Au/Graphene/Au interface. Once the graphene is hydrogenated, the electron contribution channel is closed. It is estimated that the contribution from electrons accounts for approximately 53% of the total interfacial thermal conductance for the metal/graphene/metal interfaces. Graphical abstract: